Flexitarianos no Brasil: uma análise dos fatores socioeconômicos que influenciam a redução do consumo de carne - Teixeira, Carla Djaine (2023)
Flexitarianism is a dietary model based on reducing meat consumption, which is recognized as an important ally in transitioning to sustainable food systems, capable of mitigating climate change and strengthening food security and nutrition. However, we have limited knowledge regarding the socio-economic factors associated with its adoption. The purpose of this study was to characterize the socio-economic profile of flexitarians in Brazil, examining its relationship with meat consumption patterns. We sought to answer four questions: (1) What is the sociodemographic profile of this population? (2) What are the main motivations for adopting this diet? (3) How frequently do flexitarians consume meat? (4) What are the primary meat substitutes consumed by flexitarians? Additionally, we investigated the relationship between gender, sexual orientation, and meat reduction behavior among flexitarians. Data were collected from 1029 flexitarians across Brazil using an electronic survey. Our findings indicate that flexitarianism is more prevalent among highly educated women. The primary motivation for adoption is the environmental impact of meat consumption. Consumption patterns are characterized by reduced beef consumption and increased poultry consumption. The main substitutes for meat are plant-based protein sources and eggs. Gender does not influence the degree of meat reduction among the flexitarian population, although race/ethnicity may play a role. We conclude that adopting this diet in Brazil can serve as a positive indicator and may also be related to individuals' cognitive flexibility.